2009
DOI: 10.1179/136217109x434252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of welding parameters on distribution of wire feeding elements in CO2 laser GMA hybrid welding

Abstract: The effect of welding parameters on the distribution of wire feeding elements has been investigated during CO 2 laser and pulsed gas metal arc hybrid welding process. The molten metal flow on the pool surface and inside of the samples was observed by a high speed video camera and an in situ X-ray transmission imaging system respectively. The results indicate that the fluid flow towards the inside of keyhole, namely inward flow, improves the homogeneity of weld metal. The distribution of alloying elements is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 37 publications
(42 reference statements)
2
23
0
Order By: Relevance
“…Fellmann and Kujanpää (2006) denoted that high quality joints might be produced in hybrid CO 2 laser-GMA welding of carbon steel with various compositions of the shielding gas and the best results were obtained by the addition of 2-5% CO 2 gas to helium-argon mixture. Moreover, a positive influence of oxygen addition to the shielding gas on the chemical homogeneity of the fusion zone was noted by Zhao, et al (2009). Almost homogenous distribution of alloying elements could be obtained when the oxygen content in the shielding gas was higher than 2%.…”
Section: Introductionmentioning
confidence: 92%
“…Fellmann and Kujanpää (2006) denoted that high quality joints might be produced in hybrid CO 2 laser-GMA welding of carbon steel with various compositions of the shielding gas and the best results were obtained by the addition of 2-5% CO 2 gas to helium-argon mixture. Moreover, a positive influence of oxygen addition to the shielding gas on the chemical homogeneity of the fusion zone was noted by Zhao, et al (2009). Almost homogenous distribution of alloying elements could be obtained when the oxygen content in the shielding gas was higher than 2%.…”
Section: Introductionmentioning
confidence: 92%
“…Experimental research shows that it has taken a big progress in welding of aluminium alloys and steels. [14][15][16][17] Therefore, it has the potential to join magnesium alloys well.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], it was found that a trailing gas m torch configuration helped in the mixing of the melt in the welding of 10 mm thick plates. T e approach was demonstrated in [17]. Moreover, a shielding gas containing more than 2% O2 homogeneous distribution of alloying elements in [17].…”
Section: Introductionmentioning
confidence: 97%
“…T e approach was demonstrated in [17]. Moreover, a shielding gas containing more than 2% O2 homogeneous distribution of alloying elements in [17]. One of the main reasons for uitable distribution is caused by the Marangoni effect, which mainly influences the flow behav the surfaces.…”
Section: Introductionmentioning
confidence: 99%